Urban cultures of Central Asia from the Bronze Age to the Karakhanids : learnings and conclusions from new archaeological investigations and discoveries : proceedings of the First International Congress on Central Asian Archaeology held at the University of Bern, 4-6 February 2016 - Baumer, Christoph; Novák, Mirko (2019)
Cover; Title Page; Copyright; Table of Contents; Body; Map of Central Asia with the main places mentioned in this volume; Christoph Baumer and Mirko Novák: Foreword; Turkmenistan; Lyubov B. Kircho: Altyn-Depe, The Formation of the Earliest Urban Centre in Central Asia; Nadezhda A. Dubova: Gonur Depe – City of Kings and Gods, and the Capital of Margush Country (Modern Turkmenistan). Its discovery by Professor Victor Sarianidi and recent finds...